Implementing responsible innovation: the role of the meso-level(s) between project and organisation - Bernd Carsten Stahl; Virginia Portillo; Hanne Wagner; Peter J. Craigon; Dimitrios Darzentas; Santiago De Ossorno Garcia; Liz Dowthwaite; Chris Greenhalgh; Stuart E. Middleton; Elena Nichele; Christian Wagner; Helena Webb (Journal of Responsible Innovation, 2024)
Much of academic discussion of responsible innovation (RI) has focused on RI integration into research projects. In addition, significant attention has also been paid to RI structures and policies at the research policy and institutional level. This article reports experiences of RI implementation with a focus on the intermediate i.e. meso-level. The research described here included a series of interviews that aimed to clarify researchers' perspectives on RI as well as barriers to and benefits of RI implementation. Two cases of engagement with research projects, with the aim of promoting RI, were undertaken. The analysis of the data demonstrates the crucial contribution that the meso-level of a research programme can make in interpreting, implementing and perpetuating RI across related activities. The article provides strong evidence that the scholarly debate surrounding RI should pay more explicit attention to this meso-level, ultimately strengthening RI theory and practice.